Performance indicators that predict success during counter-attacks in world cup matches - Apostolidis, N.; Armatas, V. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: It has been reported that although counter-attacks occur less frequently during soccer matches than organized attacks, they are the most effective style of play for scoring goals, especially against an imbalanced defense. Moreover, as football is a low scoring sport, general measures of offensive effectiveness such as scoring opportunities, shots on goal, and final third pitch entries have been proposed as good indicators. The present study aimed to investigate the factors associated with final third entries during counterattacks during men`s, women`s and u20 men`s World Cup (WC) matches.